CIPP-Based Analysis of Industrial Work Practice Effectiveness at a Private Vocational High School - Syaiful Kiram; Erik Junaedi; Zainal Arifin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study evaluates the effectiveness of the Industrial Work Practice Program (Prakerin) at Private Vocational High School (SMKS) TI Muhammadiyah 11 Sibuluan using the CIPP (Context, Input, Process, Product) evaluation model. The gap between vocational school graduates’ skills and industry needs remains a significant challenge for vocational education in Indonesia, while most previous studies have focused only on implementation issues without offering a comprehensive evaluation framework that addresses each school’s unique context. Employing a qualitative, evaluative approach, this research collected data through participant observation, in-depth interviews with 15 informants (including the principal, supervising teachers, industry partners, and students), and document analysis. Data validity was ensured by source and method triangulation, member checking, and peer debriefing. The findings reveal that the Prakerin program is effective in enhancing students’ technical competencies, supported by a strategic location, dual-supervision system, intensive monitoring, and comprehensive preparatory training. However, the development of soft skills—particularly leadership and initiative—remains suboptimal and requires further improvement. The implementation of a self-funding model through government grants (BOS) demonstrates strong institutional commitment and removes economic barriers for students. This study affirms the validity and relevance of the CIPP model in evaluating industrial work practice programs and provides recommendations for a more structured soft skills development strategy, as well as the innovation of sustainable industry partnership models. The novelty of this research lies in its application of a multidimensional analysis that integrates contextual, input, process, and outcome factors within the specific setting of a vocational secondary school.